Perceived Solutions for Pacifying Instructors’ Aggressive Behavior in K-12 Education - Syed Ghazanfer Abbas (Jurnal Multidisiplin Madani, 2023)
Effective teaching and learning depend on good conduct, which is also a crucial educational consequence that society should demand. If we do not deliver the good order and good results that society expects from teachers, they will become more impatient and uninformed. The main purpose of this study was to explore the aggressive behavior of educators. The objective of the study was to find out the solutions that can replace the teachers’ negative attitude with a positive attitude. Population of the study consisted of all students (621) during the year 2020-2021 from the Federal Government Boys School & Colleges, Rawalpindi. Random sampling technique was used in the selection of sample. Self-structured Questionnaire was used as a research tool with five-point Likert Scale. It is possible to improve the performance of students by changing the attitude of teachers and there is a need for training to improve teachers' professional skills. Teachers should be a part of workshops on modern teaching methods. They should provide recreational opportunities with students and should be trained to sense students' thoughts, feelings and emotions. Teachers should attend conferences to provide awareness of students' individual differences